INNOVATIVE LEADERSHIP OF ADMINISTRATORS AND TEACHERS’ QUALITY OF WORK LIFE UNDER SECONDARY EDUCATIONAL SERVICE AREA OFFICE PHETCHABURI - Klomsakun, Thanyapohn; Suksodkiew, Vorakarn (Journal of Educational Review Faculty of Education in MCU, 2025)
The purposes of this research were to determine 1) the innovative leadership of school administrators under Secondary Educational Service Area Office Phetchaburi 2) the quality of work life of teachers in educational institutions under Secondary Educational Service Area Office Phetchaburi and 3) the relationship between innovative leadership of school administrators and the quality of work life of teachers in educational institutions under Secondary Educational Service Area Office Phetchaburi. The sample group consisted of 19 educational institutions under Secondary Educational Service Area Office Phetchaburi. Six individuals were selected from each institution, including one school director, one deputy school director/assistant school director, one head of a subject group, and three teachers, totaling 114 respondents. The research instrument was questionnaire about innovative leadership based on Metcalf’s concept and quality of work life based on the framework of the Office of the Civil Service Commission. The statistical methods used for data analysis included frequency, percentage, arithmetic mean, standard deviation, and Pearson’s product – moment correlation coefficient. The research findings revealed that: 1) The overall level of innovative leadership among school administrators under Secondary Educational Service Area Office Phetchaburi was high. 2) The overall quality of work life of teachers in educational institutions under Secondary Educational Service Area Office Phetchaburi was also high. and 3) The relationship between innovative leadership of school administrators and the quality of work life of teachers in educational institutions under Secondary Educational Service Area Office Phetchaburi was found correlated in high level at .01 of statictical significance which was positive correlated.